Physiological and psychological effects of listening to Holy Quran Recitation in the Intensive Care Unit patients: a systematic review - Mat Nor, Mohd Basri; Ibrahim, Noor Airini; Ramly, Nur Fariza; Abdullah, Fa’iza (International Islamic University Malaysia * Kulliyyah of Medicine, 2019)
Stress and anxiety are common among intensive care unit (ICU) patients especially those who are on mechanical ventilation. Non-pharmacological interventions such as music and prayer are recommended because they are opioid sparing, easy to provide, cheap and safe. There is a growing body of evidence on the effects of Holy Quran Recitation (HQR) in reducing stress and anxiety in critically ill Muslim patients. The aim of this review is to evaluate the physiological and psychological effects of HQR specifically in ICU setting. This review was performed on articles published between 2007 and 2018. Extensive search was done using PubMed, ISI Web of Knowledge, Scopus and Google Scholar. Systematic review articles are also assessed and relevant literatures are hand searched based on reference lists and citations made in key publications. Studies related to HQR which were done outside adult ICU setting were excluded. A total of nine articles are included in the final list for detail analysis. Findings of this review revealed six studies with significant results in improving stress responses, hemodynamic stability and conscious levels. HQR is a potential non-pharmacological tool to reduce stress and can also be used as auditory stimulus to improve conscious level in comatose patients. More studies in this area are recommended aiming for low risk of bias, appropriate calculation of sample size and adequately powered to detect significant outcomes.